Design and implementation of semantic programming language graphical edit tool - Ye Weijun; Ying Shi; Zhao Kai; Ni Youcong (2010 International Conference On Computer Design and Applications, 2010)
SPL is a Semantic Web services oriented programming language which is based on ontology and XML. At present, it is still devoid of a platform to edit SPL program, this paper provides a tool called SPL Editor for the development of semantic program on the base of SPL language standard, and shows how to use the tool through a travel booking case. It will be quick and convenient for the programmer to complete the development of semantic program in the support of this tool.